Anterior Segment Developmental Anomalies in a 33-Week-Old Fetus with MIDAS Syndrome. (November 2014) - Herwig, Martina C.; Loeffler, Karin U.; Gembruch, Ulrich; Kuchelmeister, Klaus; Müller, Annette M.
We report anterior segment abnormalities in both eyes of a 33-week-old fetus endorsing the diagnosis of MIDAS (microphthalmia, dermal aplasia, and sclerocornea) syndrome. After abortion, the fetus was examined by a standard pediatric autopsy that included macroscopic and microscopic examination of both eyes. Postmortem findings included craniofacial stigmata (such as hypertelorism, a flat nose and low-set ears) and an agenesis of the corpus callosum. Array comparative genomic hybridization revealed a deletion of the short arm of the X chromosome (region Xp22.2 to p22.32). Ophthalmopathologic examination of the eyes revealed microphthalmia with anterior segment developmental anomalies, in particular sclerocornea and Peters' anomaly, respectively. General pathology findings plus the ocular findings allowed the diagnosis of MIDAS syndrome. A discussion of differential diagnoses is provided. This case report indicates that ophthalmopathologic investigation of fetal eyes can be of great value for the further classification of syndromes.